Childhood predictors of cardiovascular disease in adulthood. A systematic review and meta‐analysis. (25th May 2017) - Ajala, O.; Mold, F.; Boughton, C.; Cooke, D.; Whyte, M.
Summary: Childhood obesity predicts the risk of adult adiposity, which is associated with the earlier onset of cardiovascular disease [adult atherosclerotic cardiovascular disease, ACVD: hypertension, increased carotid intima media thickness (CIMT) stroke, ischemic heart disease (IHD)] and dysglycaemia. Because it is not known whether childhood obesity contributes to these diseases, we conducted a systematic review of studies that examine the ability of measures of obesity in childhood to predict dysglycaemia and ACVD. Data sources were Web of Science, MEDLINE, PubMed, CINAHL, Cochrane, SCOPUS, ProQuest and reference lists. Studies measuring body mass index (BMI), skin fold thickness and waist circumference were selected; of 1, 954 studies, 18 met study criteria. Childhood BMI predicted CIMT: odds ratio (OR), 3.39 (95% confidence interval (CI), 2.02 to 5.67, P < 0.001) and risk of impaired glucose tolerance in adulthood, but its ability to predict ACVD events (stroke, IHD; OR, 1.04; 95% CI, 1.02 to 1.07; P < 0.001) and hypertension (OR, 1.17, 95% CI 1.06 to 1.27, P = 0.003) was weak–moderate. Body mass index was not predictive of systolic BP ( r −0.57, P = 0.08) and weakly predicted diastolic BP ( r 0.21, P = 0.002). Skin fold thickness in childhood weakly predicted CIMT in female adults only (rs 0.09, P < 0.05). Childhood BMI predicts the risk of dysglycaemia and abnormal CIMT in adulthood, but its ability to predict hypertension and ACVD events was weak and moderate, respectively. Skin fold thickness was a weak predictor of CIMT in female adults.